2019
DOI: 10.1121/1.5132709
|View full text |Cite
|
Sign up to set email alerts
|

The use of nonhuman primates in studies of noise injury and treatment

Abstract: Exposure to prolonged or high intensity noise increases the risk for permanent hearing impairment. Over several decades, researchers characterized the nature of harmful noise exposures and worked to establish guidelines for effective protection. Recent laboratory studies, primarily conducted in rodent models, indicate that the auditory system may be more vulnerable to noise-induced hearing loss (NIHL) than previously thought, driving renewed inquiries into the harmful effects of noise in humans. To bridge the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 250 publications
0
8
0
Order By: Relevance
“…Each MF was repeated 30 times, resulting in blocks containing ∼300-420 trials. Experiments were performed after confirming normal hearing status through extensive audiometric and physiological characterization (ABRs, DPOAEs, otoscopy, and tympanometry), ensuring that all measures were within the range of normative values as reported in our previous work (Burton et al, 2019; Hauser et al, 2018; Stahl et al, 2022; Valero et al, 2017). Figure 1B shows how monkeys Is and Da learned to discriminate amplitude modulation frequency (MF) at various MFs in about ten sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Each MF was repeated 30 times, resulting in blocks containing ∼300-420 trials. Experiments were performed after confirming normal hearing status through extensive audiometric and physiological characterization (ABRs, DPOAEs, otoscopy, and tympanometry), ensuring that all measures were within the range of normative values as reported in our previous work (Burton et al, 2019; Hauser et al, 2018; Stahl et al, 2022; Valero et al, 2017). Figure 1B shows how monkeys Is and Da learned to discriminate amplitude modulation frequency (MF) at various MFs in about ten sessions.…”
Section: Methodsmentioning
confidence: 99%
“…When performing pharmacokinetic studies in the inner ear, the choice of an adequate model is one of the most critical issues. Even though major cochlear structures are highly conserved across species ( Burton et al, 2019 ), the size and configuration of the fluid-filled compartments vary significantly between different models ( Glueckert et al, 2018 ). While the cochlea of rhesus macaques is 24 times larger than the murine inner ear, the human cochlear volume is about three times larger than that of macaques ( Dai et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pigs, intracochlear FITC-d administration revealed that the oscillating exchange of PL and CSF via the CA plays a dominant factor in homeostasis ( Salt et al, 2015 ). Considering the significant variance of cochlear fluid spaces between different species ( Thorne et al, 1999 ), this and the longer and narrower CA in humans impedes the translation of findings from rodents to humans ( Burton et al, 2019 ). To overcome this problem, large animal models, such as non-human primates ( Balkany et al, 1980 ), cats ( Snyder et al, 1991 ), sheep ( Kaufmann et al, 2020 ) or minipigs ( Yi et al, 2014 ) have been used in inner ear research.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pig deafness models have more similarities with humans in both genetics and disease phenotypes compared to rodents (Ji et al, 2019 ). Finally, NHPs could also prove to be useful in hearing research as there are many similarities with humans, not only anatomical but also in terms of progressive hearing damage and many physiological processes and phenotypes associated with human disorders display high similarity to NHP models (Reis et al, 2017 ; Burton et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%